2019
DOI: 10.1007/s13162-019-00149-5
|View full text |Cite
|
Sign up to set email alerts
|

The digital continuum: the influence of ownership, access, control, and Cocreation on digital offerings

Abstract: Digital offerings have provided new ways to experience what once were physical products. Such offerings have upended business processes by being less costly for firms to produce, store, and distribute. The ways in which consumers access them and interact with them have called into question traditional notions of ownership, access and control. This paper extends the thinking about digital offerings by proposing a Digital Continuum framework: a conceptual model anchored at one end by Digital Products and at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Taxonomy development is well-recognized in the IS literature [31], and classification research related to digital offerings is found within data-driven digital services [32] and content-based digital products [33]. The literature explores variations in digital offerings [7], but no explicit typologies or taxonomies specific to digital offerings could be identified.…”
Section: Figure 1: Digital Offering Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Taxonomy development is well-recognized in the IS literature [31], and classification research related to digital offerings is found within data-driven digital services [32] and content-based digital products [33]. The literature explores variations in digital offerings [7], but no explicit typologies or taxonomies specific to digital offerings could be identified.…”
Section: Figure 1: Digital Offering Literaturementioning
confidence: 99%
“…Extant literature shows a tendency to treat digital services, digital products, and digital offerings as relatively synonymous concepts. The notable exception is Micken et al [7], who offers a view of digital offering variations located along a continuum anchored at one end by digital products and the other by digital services. Thereby, all services/products are seen as offerings, but not all offerings are seen as neither services nor products (i.e., offerings is an umbrella term).…”
Section: Physical Vs Digital Terminologymentioning
confidence: 99%
See 2 more Smart Citations